2015
DOI: 10.14257/ijsia.2015.9.3.25
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Android Malware Behaviors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…After doing extensive and exhaustive research, [1]. [2], [3], [4], [5], [6], [7], we have concluded that Android permission scheme/model right since its inception has been undergoing transformations and is continuously changed depending upon the user suggestions and the developer's suggestions and the platform owner's business decisions.…”
Section: Set Of Guidelines For the Permission Model In Androidmentioning
confidence: 99%
“…After doing extensive and exhaustive research, [1]. [2], [3], [4], [5], [6], [7], we have concluded that Android permission scheme/model right since its inception has been undergoing transformations and is continuously changed depending upon the user suggestions and the developer's suggestions and the platform owner's business decisions.…”
Section: Set Of Guidelines For the Permission Model In Androidmentioning
confidence: 99%